Oceanological and Hydrobiological Studies - Plinski, Marcin; SpringerLink (Online service) (Warsaw : Versita : Imprint: Versita, co-published with Springer.)
The aim of the Journal is to collect and publish in one medium the findings of worldwide studies on various types of water environment and climatic conditions. This will facilitate comparison of the studies and, in the long run, will help establish contacts and close co-operation between scientists with similar areas of interest.
Keywords: Oceanography; Marine sciences; Freshwater; Oceanography; Marine & Freshwater Sciences